Evolution of jute policies and a jute policy model for Bangladesh - Rahman, Sultan Hafeez; Research Fellow (Dhaka, Bangladesh : Bangladesh Institute of Development Studies, 1984)
The monograph begins with a discussion of the structure of the world jute economy and the economic policies pursued by the jute mandarins in Bangladesh in chapters 2 and 3. The supply bloc of the postulated model is estimated in chapter 4, while preliminary estimates of the demand parameters are obtained in chapter 5. In chapter 6, the behavioral equations of the simultaneous demand bloc are re-estimated using an appropriate estimation method.
Includes bibliographical references: p. 114-125.
ne 12/04/2019
Loans
Keywords: Jute industry; Bangladesh